The role of small airway dysfunction in asthma control and exacerbations: a longitudinal, observational analysis using data from the ATLANTIS study. Issue 7 (July 2022) - Kraft, Monica; Richardson, Matthew; Hallmark, Brian; Billheimer, Dean; Van den Berge, Maarten; Fabbri, Leonardo M; Van der Molen, Thys; Nicolini, Gabriele; Papi, Alberto; Rabe, Klaus F; Singh, Dave; Brightling, Chris; et al.
Summary: Background: Although small airway disease is a feature of asthma, its association with relevant asthma outcomes remains unclear. The ATLANTIS study was designed to identify the combination of physiological and imaging variables that best measure the presence and extent of small airway disease in asthma, both cross-sectionally and longitudinally. In this longitudinal analysis, we evaluated which small airway parameters studied were most strongly associated with asthma control, exacerbations, and quality of life. Methods: In this observational cohort study, participants with mild, moderate, or severe stable asthma were recruited between June 30, 2014, and March 3, 2017, via medical databases and advertisements in nine countries worldwide. Eligible participants were aged 18–65 years with a clinical asthma diagnosis for at least 6 months. Participants were followed up for 1 year, with visits at baseline, 6 months, and 12 months. Physiological tests included spirometry, lung volumes, impulse oscillometry, multiple breath nitrogen washout (MBNW), and percentage decrease in forced vital capacity during methacholine challenge. CT densitometry was performed to evaluate small airway disease. We examined the associations between these measurements and asthma exacerbations, asthma control, and quality of life using univariate and multivariate analyses. A composite ordinal score comprising percent predicted R5–20 (resistance of small-to-mid-sized airways), AX (area of reactance), and X5 (reactance of more central, conducting small airways at 5 Hz) was constructed. Findings: 773 participants (median age 46 years [IQR 34–54]; 450 [58%] female) were included in this longitudinal study. Univariate analyses showed that components of impulse oscillometry, lung volumes, MBNW, and forced expiratory flow at 25–75% of FVC were significantly correlated with asthma control and exacerbations (Spearman correlations 0·20–0·25, p<0·0001 after Bonferroni correction). As a composite of impulse oscillometry, the ordinal score independently predicted asthma control and exacerbations in a multivariate analysis with known exacerbation predictors. CT parameters were not significantly correlated with asthma control, exacerbation, or quality of life. Interpretation: Small airway disease, as measured by physiological tests, is longitudinally associated with clinically important asthma outcomes, such as asthma control and exacerbations. Funding: Chiesi Farmaceutici.